2017
DOI: 10.1111/1365-2745.12758
|View full text |Cite
|
Sign up to set email alerts
|

Greater root phosphatase activity in nitrogen‐fixing rhizobial but not actinorhizal plants with declining phosphorus availability

Abstract: Summary The abundance of nitrogen (N)‐fixing plants in ecosystems where phosphorus (P) limits plant productivity poses a paradox because N fixation entails a high P cost. One explanation for this paradox is that the N‐fixing strategy allows greater root phosphatase activity to enhance P acquisition from organic sources, but evidence to support this contention is limited. We measured root phosphomonoesterase (PME) activity of 10 N‐fixing species, including rhizobial legumes and actinorhizal Allocasuarina spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 80 publications
(296 reference statements)
4
79
2
2
Order By: Relevance
“…For example, Cernusak et al (2011) showed variation in the capacity for nodulation among tropical N 2 fixers, Nasto et al (2017) showed that differences in nutrient acquisition strategies between non-N 2 and N 2 fixers were driven by individual species belonging to each functional group, Zalamea et al (2016) and Png et al (2017) suggested that root phosphatase activity is phylogenetically constrained and not related to functional group or N 2 fixation, and Soper et al (2018) demonstrated a lack of a relationship between N 2 fixation, foliar N, and P acquisition among a variety of N 2 -fixing legumes, non-N 2 -fixing legumes, and non-legumes. For example, Cernusak et al (2011) showed variation in the capacity for nodulation among tropical N 2 fixers, Nasto et al (2017) showed that differences in nutrient acquisition strategies between non-N 2 and N 2 fixers were driven by individual species belonging to each functional group, Zalamea et al (2016) and Png et al (2017) suggested that root phosphatase activity is phylogenetically constrained and not related to functional group or N 2 fixation, and Soper et al (2018) demonstrated a lack of a relationship between N 2 fixation, foliar N, and P acquisition among a variety of N 2 -fixing legumes, non-N 2 -fixing legumes, and non-legumes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cernusak et al (2011) showed variation in the capacity for nodulation among tropical N 2 fixers, Nasto et al (2017) showed that differences in nutrient acquisition strategies between non-N 2 and N 2 fixers were driven by individual species belonging to each functional group, Zalamea et al (2016) and Png et al (2017) suggested that root phosphatase activity is phylogenetically constrained and not related to functional group or N 2 fixation, and Soper et al (2018) demonstrated a lack of a relationship between N 2 fixation, foliar N, and P acquisition among a variety of N 2 -fixing legumes, non-N 2 -fixing legumes, and non-legumes. For example, Cernusak et al (2011) showed variation in the capacity for nodulation among tropical N 2 fixers, Nasto et al (2017) showed that differences in nutrient acquisition strategies between non-N 2 and N 2 fixers were driven by individual species belonging to each functional group, Zalamea et al (2016) and Png et al (2017) suggested that root phosphatase activity is phylogenetically constrained and not related to functional group or N 2 fixation, and Soper et al (2018) demonstrated a lack of a relationship between N 2 fixation, foliar N, and P acquisition among a variety of N 2 -fixing legumes, non-N 2 -fixing legumes, and non-legumes.…”
Section: Discussionmentioning
confidence: 99%
“…Various legume species in south-western Australia form both AM and ECM along with N 2 -fixing nodules (Albornoz et al 2016a;Brundrett 2009;Png et al 2017), giving rise to the possibility for an elaborate guild of structures for nutrient exchanges between plants that have never been documented (Fig. 4).…”
Section: Nutrient Exchange-based Facilitationmentioning
confidence: 99%
“…These N 2 -fixing plants are P sinks at this early stage, and may meet their P requirements with the help of scavenging mycorrhizal hyphae and/or the intermingling of roots around cluster roots of neighbouring P-mining species ). Such scavenging may represent an efficient strategy for obtaining P in extremely P-impoverished soils; legumes also show higher root phosphatase activity than co-occurring non-legume species, suggesting that they are particularly good at acquiring organic P (Png et al 2017). Both AM and EM fungi could access newly mobilised P from cluster root 'burst' microsites, but EM may be favoured, since they possess highaffinity P transporters at their mycelia front (Cairney 2011).…”
Section: Nutrient Exchange-based Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Houlton et al () and other studies that have contrasted fixing and nonfixing plants have generally found that phosphatase enzyme production is elevated in the roots and rhizospheres of N 2 ‐fixing legumes (Houlton et al, ; Nasto et al, ; Png et al, ) potentially because they have more N available to invest in enzyme synthesis. Alternatively, there is evidence that phosphatase enzyme production is not dependent on N supply from fixation, but rather may be a phylogenetically conserved trait between groups or species (Png et al, ).…”
Section: Introductionmentioning
confidence: 98%